Pengaruh Penggunaan Alat Komunikasi Terhadap Kelainan Refraksi Miopia Di Puskesmas Ulak Karang Kota Padang - Amir, Amril; Saunir , Ihsan (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2024)
This scientific paper discusses the influence of the use of communication tools on myopia refractive disorders at the Ulak Karang Community Health Center, Padang City. This study aims to find out: (1) whether there is an influence of gadget use on myopia refractive errors at the Ulak Karang Community Health Center in the city of Padang. (2) determine the factors causing the use of gadgets to increase the degree of myopia refractive error at the Ulak Karang Community Health Center in the city of Padang. This research uses quantitative descriptive methods. The population in this study were all purely optical patients in Padang City with a sample of all patients who experienced myopia caused by gadgets, namely 40 respondents. Data was collected through a questionnaire, then the data was discussed in accordance with the theory proposed in the literature review. The results of this research showed that the average frequency of respondents who answered the questionnaire items with the answer "Yes" which indicated myopia refractive error due to the influence of gadgets was 30 people with a percentage of 75%. The total average frequency of respondents who answered the questionnaire items "No" was 10 people with a percentage of 25%. Based on the research results, it can be seen that 28 (85%) people play gadgets for quite a long time and 12 (15%) people rarely use gadgets. The high percentage of people who use gadgets for a long time can be seen from the answers. Most people nowadays can't be separated from gadgets, whether it's to search for information or to play games or so on. Apart from all that, we have to keep our eyesight in check so that we don't experience interference.